2021
DOI: 10.3390/pathogens10121640
|View full text |Cite
|
Sign up to set email alerts
|

Genotyping and Antimicrobial Susceptibility of Clostridium perfringens and Clostridioides difficile in Camel Minced Meat

Abstract: The present study aimed to determine the occurrence, genotypes, and antimicrobial resistance of Clostridium perfringens (C. perfringens) and Clostridioides difficile (C. difficile) in camel minced meat samples collected from small butcher shops and supermarkets in Al-Ahsa Governorate, Saudi Arabia. A total of 100 camel minced meat samples were randomly collected from small butcher’s shops (n = 50) and supermarkets (n = 50) in Al-Ahsa Governorate, Saudi Arabia. C. perfringens and C. difficile were isolated and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 68 publications
1
13
0
Order By: Relevance
“…A recent study reported the isolation from faeces of South American camelids of unknown health status from seven farms in Germany 13 . Moreover, it was previously isolated from Old World Camels’ minced meat 14 as well as camel faeces 15 in Saudi Arabia and Iran. The presence of this bacteria in the amputated leg's culture of the alpaca in this case report is quite significant for herd prevalence information, as well as for zoonotic purposes, as C. difficile is a bacterium whose prevalence in the United Kingdom is currently unknown.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study reported the isolation from faeces of South American camelids of unknown health status from seven farms in Germany 13 . Moreover, it was previously isolated from Old World Camels’ minced meat 14 as well as camel faeces 15 in Saudi Arabia and Iran. The presence of this bacteria in the amputated leg's culture of the alpaca in this case report is quite significant for herd prevalence information, as well as for zoonotic purposes, as C. difficile is a bacterium whose prevalence in the United Kingdom is currently unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Limited research studies in KSA investigated the resistance and occurrence of C. perfringens in camel meat. They showed these bacteria’s high resistance to tetracycline and ceftiofur drugs and, to a lesser extent, other antimicrobial agents (erythromycin, oxytetracycline, penicillin, metronidazole, clindamycin, and lincomycin) [ 12 , 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mostly, they were related to single-domain camelid antibodies as a therapeutic option for CDI (13 articles). Three articles investigated C. difficile and its prevalence in camels [21][22][23]. C. difficile was found in two of these studies, none of these research articles described C. difficile in SAC.…”
Section: Clostridioides Difficile and (South American) Camelids In Li...mentioning
confidence: 99%
“…All isolates were positive for toxin B, three isolates were positive for toxin A. AST was performed by broth microdilution for seven different antimicrobial agents (ceftriaxone, TET, CLI, MEZ, PEN, MOX and AMC). The isolates showed different antimicrobial resistance patterns (TET, CLI + TET, ceftriaxone + TET, PEN + ceftriaxone + MOX) [21].…”
Section: Clostridioides Difficile and (South American) Camelids In Li...mentioning
confidence: 99%